2005
DOI: 10.1108/14720700510630013
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility in Portugal: empirical evidence of corporate behaviour

Abstract: Purpose -The purpose of this research is to explore corporate social responsibility (CSR) evidence and, especially, the experience and practice of enterprises in Portugal.Design/methodology/approach -As a generally accepted principle, the corporate social report is a communication and measurement object. But there are limitations concerning availability and accuracy of the data that could create constraints and diminish the scope of this report. Thus, the methodology for this paper is subdivided into two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 28 publications
1
43
0
3
Order By: Relevance
“…The stakeholder approach [34][35][36][37] Jamali [68,69], led to the identification of the following six stakeholder categories: "human resources", "shareholders", "community", "environment", "suppliers", and "consumers", based on the model developed by [39]. These categories are similar to those identified by [34] (employees, suppliers, customers, community) and [37] (employees, consumers, community, investors, suppliers, environment).…”
Section: Hypothesesmentioning
confidence: 95%
“…The stakeholder approach [34][35][36][37] Jamali [68,69], led to the identification of the following six stakeholder categories: "human resources", "shareholders", "community", "environment", "suppliers", and "consumers", based on the model developed by [39]. These categories are similar to those identified by [34] (employees, suppliers, customers, community) and [37] (employees, consumers, community, investors, suppliers, environment).…”
Section: Hypothesesmentioning
confidence: 95%
“…Considering the scarcity of similar research in Spain, it is better to have imperfect evidence that could improve our understanding of the situation as opposed to no evidence at all (Abreu et al, 2005). However, further research using a larger sample size should be carried out to confirm the findings of this paper.…”
Section: Asset Managers and Analystsmentioning
confidence: 71%
“…They concluded that a considerer number of Portuguese companies have a code of conduct and that most of the managers of companies without codes of conduct considered important to have this code and spread it within their organization. Abreu and Crowther (2005) have analyzed SR in Portugal empirically. Their findings show the relationship between SR activity and corporate image and performance and also, the existence of cultural differences in SR conceptualization.…”
Section: The Study Contextualizationmentioning
confidence: 99%